Hydroformylation of Higher Olefins in Aqueous Biphasic Medium Using Rhodium-Sulfoxantphos Catalyst: Activity and Selectivity Study - Pagar, Nitin S.; Deshpande, Raj M. (Asian Journal of Chemistry, 2020)
Hydroformylation of higher olefins such as 1-hexene, 1-octene, 1-decene and 1-dodecene has been studied in an aqueous biphasic medium using water-soluble Rh-sulfoxantphos complex catalyst. The effect of temperature, presence of various co-solvents and concentration of co-solvent on the reaction rate and chemo and regioselectivity was investigated. N-Methyl pyrrolidone (NMP) was found to be the best co-solvent, which enhances the rate dramatically (4-96 fold) as compared to the reactions in aqueous-organic biphasic medium for hydroformylation of higher olefins. Catalyst recycle study was performed to check the leaching of metal in organic phase.